Two Cases of Pneumatosis Intestinalis during Cetuximab Therapy for Advanced Head and Neck Cancer - James A. Miller; Daniel J. Ford; Mohamed S. Ahmed; Thom R. Loree (Case Reports in Oncological Medicine)
Pneumatosis intestinalis is a rare but known potential complication of treatment with cetuximab. Here we present two cases of pneumatosis intestinalis occurring in patients who were receiving cetuximab as treatment for advanced head and neck cancer. In both cases, cetuximab was discontinued after discovery of the pneumatosis intestinalis.